CYBERNETIC MODELING OF TEACHER – STUDENT COMMUNICATION - MĘCZYKOWSKI Dariusz (2018)
The research focuses on social system and general regularities (relations), typical and repetitive in them (among human beings as an exemplification of elementary objects). The main goal of the author is to indicate the possibility of modeling and optimizing the relationships (communication) teacher-student – or relationship coach-player – using the cybernetics research workshop. This epistemological-methodological convention results from the fact that system-cybernetic methods allow to describe and explain the phenomena under consideration in a different light, give them a new, wider meaning, draw conclusions that would often be impossible to derivefrom other sciences. Moreover, their utilitarian significance is expressed in the accuracyof formulating answers to the questions posed by practitioners. A significant result of the research process is also the determination of the conditions of sufficient and necessary efficiency and the effectiveness of communication between the objects indicated. They constitute general, typical and repeatable regularities. Therefore, ignoring them can only cause conflicts and social rebellions. In order to prevent them and maximize the effects of any training (information and energy), you must undoubtedly educate teachers and trainers in the field of sociocybernetics and psychocybernetics. The elements signaling and initiating such a process are contained in this text.